Electrophoretic Differences in the Capsid Proteins of Simian Virus 40 Plaque Mutants - Barban, Stanley (1973)
The structural proteins of three mutants of simian virus 40 (SV40) which differ in plaque size, temperature sensitivity, oncogenicity, host cell restriction, and immunological properties were studied. The polypeptide components of these SV40 strains could not be distinguished by their polyacrylamide gel electrophoretic patterns. When the dissociated virions of two of the mutants were analyzed by the isoelectric focusing technique in a urea gradient, the capsid protein peaks were found to differ significantly in their isoelectric points. The capsid protein of the small-plaque mutant had an isoelectric point of pH 6.51 as compared with pH 6.28 for the large-plaque strain. Isoelectric focusing of the isolated capsid protein revealed three components, a single major subunit and two minor forms. The coat proteins of two of the mutants, small-plaque and minute-plaque strains, were indistinguishable by this technique. The capsid protein peaks obtained by isoelectric focusing were further analyzed by polyacryalmide gel electrophoresis.